Interior morphology of high-performance polyethylene fibers revealed by modulus mapping. (26th October 2016) - Strawhecker, Kenneth E.; Sandoz-Rosado, Emil J.; Stockdale, Taylor A.; Laird, Eric D.
Abstract: This work elucidates the undisturbed interior morphology of commercial ultra-high-molecular-weight polyethylene (UHMWPE) high-performance fibers through atomic force microscopy (AFM) modulus mapping of interior surfaces exposed by a novel focused ion beam (FIB)-notched sample preparation technique. The imaging shows unequivocally the presence of epitaxial crystals in the interior of highly drawn UHMWPE fibers. Overall, AFM observations and measurements were made for three different commercial fiber types, illustrating five basic UHMWPE morphologies: (i) extended chain fibrils (shish), (ii) interlocking and (iii) standalone kebab or epitaxial crystals, (iv) voids or interface between fibrils, and (v) tie chains across voids. Furthermore, microfibrils were bundled into groups separated by voids or amorphous material. Bundled groups of microfibrils group together to form macrofibrils, typically separated by larger voids or amorphous material. Additionally, stretched tie-chain bridges provide connectivity between some fibrils. Each of these five features (extended chain fibrils, interlocking and standalone epitaxial crystals, voids and tie-chains) varies across the three types of commercial fibers, and sometimes across the individual fiber interiors. AFM contact modulus values measured transverse to the fiber draw axis were found to vary considerably within different morphological domains. The distribution of morphology sizing was quantified for each of the examined fibers. The measurement of internal facets have major implications for fiber modeling and processing, such as optimization of draw ratios to affect the extent and arrangement of epitaxial crystalline morphologies and thus improve mechanical performance. Graphical abstract: Highlights: UHMWPE fiber interior morphology detailed through AFM nano-mechanical mapping. Clear evidence of epitaxial crystals, voids, and tie-chains in commercial fibers. Novel focused-ion-beam sample prep and multi-frequency AFM techniques applied.